Traditional Indonesian carved ornaments in Rancakan contemporary gamelan to support fine arts learning - Hermanto, Bambang; Ponimin, Ponimin; Rahayuningtyas, Wida; Zulkifli, Norzizi (Fakultas Sastra Universitas Negeri Malang, 2024)
The teaching process in the form of teaching, training and research can be a means to strengthen steps in living in the world so that achievements in the fields of knowledge and skills are expected by everyone, namely a way to fully enjoy life based on the world. These human needs and desires can be fulfilled by the emergence of creative thinking ideas and innovative thinking ideas which are achieved by studying one's education. The aim of this research is to increase students' love for Indonesian culture through